TOWARD A THEORY OF NEW NATURAL LAW AS A BASIS FOR FUTURE LEGAL POSITIVISM (Revista Paradigma, 2016)
Legal positivism is succumbing in ethical neutrality, being based on formal procedures only. Criteria for judging procedures are based on further procedures, leading to ever increasing complexity and decreasing content. This long term development in legal positivism is based first on the development of dogmatic positivism linked to the empiricism in the natural sciences, during the eighteenth century, and secondly on the development of dynamic positivism in the empirical social sciences, during the second half of the nineteenth century. Together, these have led to dynamism in legal positivism, not linked any more to basic constants - in society and human nature or ethics and religion - as were present in natural law. Legal positivism will only have a future in shaping long term development of society if, antithetically, it succeeds to disentangle itself from its present inherent dynamism. This will enhance a new theory about the durability and stability of human relations i.e. about a new concept of natural law. The basic outline of this new natural law emerges from the qualitative analysis of main patterns in society, not as empiricist analysis but as idealised ordering principles, reducing endless empirical variation to structured, manageable lines of reasoning.